Zona Bahaya Di Jalan Raya: Analisis Mendalam Kecelakaan Lalu Lintas di Jalur Bontang-Samarinda - Zainul, L.M; Abdisa, Hapnal; Maslina, Maslina; Hardiyono, Hardiyono; Rusba, Komeyni; Nurhidayati, Wa Ode (Institut Transportasi dan Logistik Trisakti, 2024)
This study examines the characteristics of traffic accidents on Bontang-Samarinda route during the period of 2018-2020 to identify the accident patterns, causal factors, and accident-prone locations. The data were collected from the police records including time of occurrence, type of casualty, type of vehicle, type of collision, and causal factors. The analysis shows that accidents tend to occur in the afternoon and evening, with a pre-dominance of accidents involving two-wheeled vehicles. The most common type of casualty was minor injuries, but there was an increase in cases of serious injuries in 2020. The main contributing factors were high-speed and road marking violations, with straights and turns being common maneuver. Most crashes occurred in certain segments, especially at KM 22-28 and KM 64-70. This research methods is EAN weighting. The study concludes that prevention efforts should focus on the speed regulation, the driver awareness, and the infrastructure improvement in high-risk road segment. These results provide important guidance for policy makers and relevant authorities to develop more effective road safety strategies on Bontang-Samarinda route.